PENERAPAN METODE DESIGN THINKING UNTUK MENINGKATKAN KEMAMPUAN KREATIVITAS DAN KEMAMPUAN PEMECAHAN MASALAH SISWA SEKOLAH DASAR - Eka Grana Aristyana Dewi; Ni Wayan Nanik Suaryani Taro Putri; I Wayan Pasek Bagus Adi Wijaya; Muhammad Assegaf; Sydney Metaliana Dos Santos Narciso; Muhamad Iqbal Ar’rayyan (LPPI UMN AL WASHLIYAH, 2026)
This community service activity aims to enhance the creativity of students at SD Negeri 3 Renon, Denpasar, with the implementation of the Design Thinking framework. The background of this activity is based on the limited ability of students to think creatively and develop solutions to learning-related problems. The activity involved 50 fifth-grade students and was conducted over four learning sessions. The method used was a participatory approach, in which students were actively engaged in the five stages of Design Thinking: empathize, define, ideate, prototype, and test. The implementation was carried out through structured learning activities that encouraged students to identify problems, generate ideas, and design as well as test simple solutions. Evaluation was conducted using observation sheets and a creativity assessment rubric. The results showed an improvement in the average creativity score from 62 (moderate category) to 81 (good category). In addition, 85% of students demonstrated increased confidence in expressing their ideas and the ability to produce innovative solutions.In conclusion, the application of Design Thinking has proven to be effective in enhancing students’ creativity and critical thinking skills at the elementary school level, and it has the potential to serve as an innovative learning approach